Association Between Previous Stroke and Severe COVID-19: A Retrospective Cohort Study and an Overall Review of Meta-Analysis - Huang, Huayao; Chen, Junnian; Fang, Shuangfang; Chen, Xiaoling; Pan, Xiaobin; Lei, Hanhan; Zhang, Yixian; Lin, Hailong; Yuan, Qilin; Xia, Pincang; Liu, Nan; Du, Houwei (Frontiers in Neurology, 2022)
Objective The objective of this study was to investigate the association between previous stroke and the risk of severe coronavirus disease 2019 (COVID-19). Methods We included 164 (61.8 ± 13.6 years) patients with COVID-19 in a retrospective study. We evaluated the unadjusted and adjusted associations between previous stroke and severe COVID-19, using a Cox regression model. We conducted an overall review of systematic review and meta-analysis to investigate the relationship of previous stroke with the unfavorable COVID-19 outcomes. Results The rate of severe COVID-19 in patients with previous stroke was 28.37 per 1,000 patient days (95% confidence interval [CI]: 10.65–75.59), compared to 3.94 per 1,000 patient days (95% CI: 2.66–5.82) in those without previous stroke (p < 0.001). Previous stroke was significantly associated with severe COVID-19 using a Cox regression model (unadjusted [hazard ratio, HR]: 6.98, 95% CI: 2.42–20.16, p < 0.001; adjusted HR [per additional 10 years]: 4.62, 95% CI: 1.52–14.04, p = 0.007). An overall review of systematic review and meta-analysis showed that previous stroke was significantly associated with severe COVID-19, mortality, need for intensive care unit admission, use of mechanical ventilation, and an unfavorable composite outcome. Conclusion Previous stroke seems to influence the course of COVID-19 infection; such patients are at high risk of severe COVID-19 and might benefit from early hospital treatment measures and preventive strategies.